O que é literatura? Provocações metalinguísticasem narrativas de Luci Collin - Lúcia Osana Zolin (Estudos de Literatura Brasileira Contemporânea)
Several initiatives within literary theory and criticism have been endeavored toestablish the frontiers of literature. Every new historical and literary contextbrings forth new expectations with regard to the literary text and consequentlynew evaluation criteria. Contemporary Brazilian literature, produced within theso-called post-modernity and marked by diffidence in universal discourses, hasreflected upon itself to problematizefrontiers, cross-roads and intersectionsestablished with other languages. The current paper discusses the metafiction inthe short stories of Luci Collin. The theoretical interdisciplinary perspective isforegrounded on post-structuralist thought.